Is the First-Past-the-Post Necessarily the First?. (June 2018) - Chakrabarty, Arijit
In this short note, the probability of the event that in a first-past-the-post voting system, the party winning the maximum number of seats loses in terms of popular votes, is studied under a few simplifying assumptions. It turns out that the said probability is roughly 20 per cent. That is, one-fifth of the times, the said event will happen, on the average. JEL Classifications: D04, D72, D78